PENGELOLAAN DANA DESA (EX. KECURANGAN) - Ferry Endah Aryati; Aprina Nugrahesthy Sulistya Hapsari (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2018)
This study iams to compared the stages of financial management in Bringin Village and Popongan Village, Bringin District,Semarang Regency and to see the potential and fraudulent motives in the management of village funds from planning, implementation, administration to reporting and accountability. The data is obtained from interview of icials village and field observation. The research method used is descriptive qualitative approach, the results reveal that the two villages have passed village fund management in accordance with government regulations. In addition, external parties also conduct monitoring through internal and on-going monev, the village of icials has been tightened in the management of village funds such as conducting detailed supervision in the management of village funds.